“Querida Amazonia” : The emergence of a genetic-inductive hermeneutics and the theological-cultural inculturation of the doctrine - Luciani , Rafael (Razón y fe, 2020)
Pope Francis has promoted the beginning of a process of creative reception of Vatican II. Rather than reforming ecclesial structures, he sought to convert mentalities and redirect institutional modes of procedure in the light of a model of the missionary and synodal Church. We can speak of a Church in transition, characterized by the coexistence of different ecclesiological models that have given rise to debates about the hermeneutics of the Council’s statements and the evolution of the magisterium. The discussions on the new Apostolic Exhortation “Querida Amazonia” (QA) took place at this crossroads. In this space, we would like to offer some criteria for the interpretation of the synodal process and the reception that begins in this new hour for the Latin American Church.